WhatsApp and Youtube: Buddies for Biology Learning Media During the COVID-19 Pandemic - Rizalia, Syarif; Nurannisa Syam, Andi; Cahya Adi , Widi (KnE Social Sciences, 2022)
This study sought to determine the effectiveness and efficiency of using WhatsApp and YouTube for biology learning media during the COVID-19 pandemic. The data were collected from students in semester 4 of the 2019/2020 academic year who attended biology learning media courses at IAIN Kendari’s Biology Tadris Department. The ex-post facto method was used to interpret the current situation as the result of various factors that occurred previously, then to analyze and determine a solution for the current situation using a SWOT analysis. The finding showed that WhatsApp and YouTube could be used as teaching media in biology courses. While this proved to be an effective method, it became less effective due to an unstable internet network in student areas and high internet quota costs. The SWOT analysis revealed a number of challenges that were quickly addressed by internal (campus) and external (ministries) parties by lowering tuition fees and providing free internet quotas for students and lecturers. Based on this, it is possible to conclude that WhatsApp and YouTube can serve as ‘buddies’ for the COVID-19 pandemic’s biology learning media courses. Keywords: WhatsApp, YouTube, biology learning media, pandemic